2020
DOI: 10.3390/jcm9082657
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Drusen Volume Assessed by Two Different OCT Devices

Abstract: To compare drusen volume between Heidelberg Spectral Domain (SD-) and Zeiss Swept-Source (SS) PlexElite Optical Coherence Tomography (OCT) determined by manual and automated segmentation methods. Thirty-two eyes of 24 patients with Age-Related Macular Degeneration (AMD) and drusen maculopathy were included. In the central 1 and 3 mm ETDRS circle drusen volumes were calculated and compared. Drusen segmentation was performed using automated manufacturer algorithms of the two OCT devices. Then, the automated segm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
1
5
0
2
Order By: Relevance
“…Участки ГА с выраженной гипоаутофлуоресценцией выявлены у 23 % (10 человек, 17 глаз), среди которых унифокальные области ГА были у 8 % (3 человека, 6 глаз), мультифокальные области ГА -у 15 % (7 человек, 11 глаз). Данные изменения были описаны в работах других авторов [20][21][22][28][29][30].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Участки ГА с выраженной гипоаутофлуоресценцией выявлены у 23 % (10 человек, 17 глаз), среди которых унифокальные области ГА были у 8 % (3 человека, 6 глаз), мультифокальные области ГА -у 15 % (7 человек, 11 глаз). Данные изменения были описаны в работах других авторов [20][21][22][28][29][30].…”
Section: Discussionunclassified
“…Достаточно исчерпывающую и точную информацию о состоянии сетчатки нам дает оптическая когерентная томография (ОКТ) [16][17][18][19][20][21][22][23]. Однако исследований, которые посвящены использованию ОКТ с аутофлуоресценцией (АФ) глазного дна при сочетании миопии высокой степени с разными стадиями ВМД, практически нет [24][25][26][27][28].…”
unclassified
“…This fact makes it difficult to compare measurements between equipment from different brands as well as with implementations based on recent research. For example, as addressed in [ 25 ], the authors highlight the differences in manual and automated segmentation in drusen volume from a Heidelberg spectral domain (SD-) and a Zeiss swept-source (SS) PlexElite optical coherence tomography (OCT).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the segmentation and analysis of retinal layers in OCT images and their clinical implications have focused the efforts of many researchers [ 22 ]. Besides the RNFL, researchers particularize their methods to detect and segment in OCT images some retinal abnormalities such as exudate-associated derangements [ 23 ], drusen volume [ 24 , 25 ], neovascularizations [ 26 ], intraretinal cysts [ 27 ], or to assess the presence and quantity of intraretinal and subretinal fluids [ 28 ] and image-guided treatment management [ 29 , 30 ]. Focusing on the RFNL, it was initially differentiated from other retinal layers in OCT imaging using a thresholding algorithm that detected the anterior edge of retinal pigment epithelium and determined the photoreceptor layer position.…”
Section: Introductionmentioning
confidence: 99%
“…Improved visualization of external layers with SS-OCT devices, provides better automated segmentation performances, and more concordance in manual and automated measurements of drusen volume. Even more, some authors found no significant differences in drusen volume prior to and after manual correction in SS-OCT compared with a significant difference in SD-OCT devices [38].…”
Section: Drusen Volumementioning
confidence: 94%